Caracterização de novos genes candidatos associados com tolerância ao alumínio em milho e validação de um QTL de efeito maior para tolerância ao alumínio no aumento de produtividade de grãos - Renato Coelho de Castro Vasconcellos (2012)
Al toxicity is a major limiting factor for root growth in acid soils, leading to serious problems in crop production, especially in tropical and subtropical regions. The development of Al-tolerant genotypes is a sustainable alternative to overcome the constraints caused by Al toxicity. Aluminum tolerance in maize is a complex trait involving multiple genes and mechanisms that have not been fully elucidated yet. This study was divided in two objectives: a) characterization of novel candidate genes associated with Al tolerance in maize, and b) validating the effect of a major Al tolerance QTL on maize yield performance. In the first chapter, we conducted a search for predicted genes in the maize genome using genes previously involved in Al tolerance in other species. Candidate genes sharing high protein similarity levels to the STOP1, SbMATE and Nrat1. However, these candidate genes were not co-localized in the confidence intervals of Al tolerance QTLs previously identified. Due to the high level of sequence similarity between Nrat1 from rice and ZmNrat1, the expression of this maize candidate gene was further evaluated. ZmNrat1 showed root specific expression, and a differential overexpression of 1 to 72 hours after Al treatment in both regions of the seminal root. This expression pattern was highly compatible with the Nrat1 expression, suggesting a putative relationship of orthology between those genes. Although, we could not conclude about the involvement of ZmNrat1 in maize Al tolerance. In the second study, the introgression of an Al tolerance QTL (qALT6) improved significantly the grain yield on maize near-isogenic lines in soils with 20% and 40% of Al saturation. Additionally, qALT6 showed a positive effect in most of the hybrid combinations with elite lines from the maize breeding program of Embrapa, regarding to grain yield mainly in soils with high Al saturation (40%). Although the field experiment was performed in only one environment, these preliminary results suggest that introgression of qALT6 using marker-assisted selection may result in a significant improvement on maize yield stability in acidic soils.